P073 Co-morbid insomnia and obstructive sleep apnoea is associated with all-cause mortality and cardiovascular event risk. (7th October 2021) - Lechat, B; Appleton, S; Melaku, Y; Hansen, K; McEvoy, R; Adams, R; Catcheside, P; Lack, L; Eckert, D; Sweetman, A
Abstract: Introduction: Co-morbid insomnia and sleep apnoea (COMISA) is a highly prevalent and debilitating condition. Previous studies have investigated associations between insomnia and mortality, and OSA and mortality, but not COMISA. Thus, this study investigated associations between OSA, insomnia and COMISA on mortality and cardiovascular event risks. Methods: Sleep Heart Health Study data (n = 5803) were used to identify people with insomnia defined as difficulties falling asleep, maintaining sleep, and/or early morning awakenings from sleep at least 5 times a month and daytime impairment. OSA was defined as an apnoea-hypopnoea index ≥15 events/h. COMISA was defined if both conditions were present. Cox proportional hazard models were used to determine the association between COMISA and all-cause mortality (n = 1210) and cardiovascular events (N = 1243) over 15 years of follow-up. Results: This analysis included 5236 participants. 2504 (47.8%) did not have insomnia/OSA, 374 (7.1%) had insomnia-alone, 2027 (38.7%) had OSA-alone, and 331 (6.3%) had COMISA. Compared to participants with no insomnia/OSA, COMISA was associated with a 32% (HR, 95%CI; 1.32 (1.06, 1.64)) and 38% (1.38 (1.11, 1.71)) increased risk of mortality and cardiovascular events, respectively. Insomnia-alone and OSA-alone were not associated with all-cause mortality or cardiovascular event risk. Conclusions: Participants with COMISA have decreased longevity and increased cardiovascular event risks compared to participants with no insomnia or OSA. It remains to be determined if these associations are causal and whether treatment of insomnia, OSA, or combination treatment can effectively decrease mortality and/or cardiovascular event risks in individuals with COMISA.